A salute to America on its two-hundredth anniversary - Hamarneh, Sami Khalaf, 1925- (Islamic Center, 1976)
A descriptive brochure prepared on the occasion of the opening ceremonies of the Islamic Bicentennial Exhibition at the Islamic Center, Washington, D.C. sponsored by the Supreme Council for Islamic Affairs, Egypt.